A comparative study of structural and conformational properties of WNK kinase isoforms bound to an inhibitor: insights from molecular dynamic simulations. Issue 3 (2nd February 2022) - Jonniya, Nisha Amarnath; Sk, Md Fulbabu; Kar, Parimal
Abstract: The with-no-lysine (WNK) kinase causes pseudohypoaldosteronism type II, a genetic form of hypertension. Due to ∼80% similarity among four isoforms (WNK1/2/3/4) of the WNK protein family, the discovery of an ATP-competitive inhibitor renders a significant challenge. Here, we combined molecular modeling and molecular dynamics simulations to study the structural and conformational properties of the WNK kinase isoforms bound to an ATP competitive inhibitor (WNK463). We have also investigated the effect of phosphorylation on the conformational properties of each isoform. The largest deviation of Cα atoms is observed for the unphosphorylated uWNK4 complex, while the least deviation is obtained for uWNK3. The G-loop and αC-helix regions are also more flexible in uWNK4 compared to the other three unphosphorylated isoforms. However, in uWNK1, the A-loop region is the most flexible compared to other complexes. In all cases, phosphorylation stabilizes different regions of the protein–inhibitor complexes. In the case of uWNK4, relatively higher anti-correlated motions are observed compared to the other three unphosphorylated complexes. Furthermore, in the case of uWNK4, the distance between N- and C-lobes is found to be slightly higher than other complexes. This distance is reduced in all four complexes after the phosphorylation. Principal component analyses suggest that the phosphorylation leads to structural stabilization in WNK1 and WNK4, while it causes more flexibility in WNK2 and WNK3. Overall, our study provides comprehensive and comparative information on the structural dynamics of the WNK isoform family with the known competitive inhibitor that would aid in the development of a new inhibitor. Communicated by Ramaswamy H. Sarma